Timed Petri nets in modeling and analysis of cluster tools. - Zuberek, W.M (IEEE Transactions on robotics and automation)
Timed Petri nets are used as models of cluster tools representing the flow of wafers through the chambers of the tool as well as sequences of actions performed by the robotic transporter. Since the durations of all activities are also represented in the model, performance characteristics can be derived from the model for steady-state, as well as transient behaviors. The performance of single-blade tools is compared with that of dual-blade tools. The effects of multiple loadlocks, redundant chambers and multiple robots are discussed and, analyzed. Modeling of wafer routings with chamber revisiting and processing of wafers of multiple types is also briefly discussed